Industrial customisation of digital human modelling tools. (28th March 2008) - Hogberg, Dan; Backstrand, Gunnar; Lamkull, Dan; Hanson, Lars; , Roland Ortengren
Computer aided visualisation and simulation enables early evaluation of important design parameters of future products and production systems. Typically, humans affect the system performance, and in order to achieve the expected system efficiency ergonomics needs to be considered in the design process in addition to the more technical or logistical matters. Hence, there is a call for ergonomics to be a natural part of the product and production development process, also at virtual stages. Three examples of the development of Digital Human Modelling-(DHM)-based company-specific ergonomics evaluation methods and work processes are portrayed, argued and discussed. These illustrate the use of DHM tools for performing static work and occupant packaging analyses, as well as customising activities made for the implementation of the tools in companies' work processes. This is followed by a discussion of future needs of DHM tools including the call for ergonomics methods for evaluating full work cycles.